Điều khiển bền vững tối ưu bình phương với phản hồi đầu ra - Hỷ, Chu Văn (Journal of Computer Science and Cybernetics, 2016)
This paper presents the quadratic control ot output feedback systems with uncertain parameters by using a parameter optimization technique. An algorithm for the numerical solutions is  available. The case where we know only the statistical properties of initial states is also considered.